2002
DOI: 10.1051/apido:2002024
|View full text |Cite
|
Sign up to set email alerts
|

Differential infestation of honey bee, Apis mellifera, worker and queen brood by the parasitic mite Varroa destructor

Abstract: -We examined the distribution of Varroa destructor on worker and queen brood in colonies of A. mellifera. With both worker and queen hosts present, the mite prevalence value for worker hosts was 75.0 ± 4.0% (lsmean ± SE), compared to 5.1 ± 4.0% for queen hosts (P < 0.0001). We also examined the response of mites to cuticular extracts of 5th instar worker and queen larvae using arrestment bioassays. In binary-choice tests at 0.5 larval equivalents (Leq), worker extract arrested 84.79 ± 4.98% of the mites, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Queen larvae and extracts of queen larvae were significantly less attractive than worker and drone larvae, and the royal jelly of the queen larvae even had a repellent effect (Calderone and Lin, 2001;Calderone et al, 2002;Trouiller et al, 1994). Nazzi et al (2009) confirmed these results for octanoic acid, which is present in higher quantities in royal jelly than in the food of worker or drone larvae.…”
Section: Orientation and Host Findingmentioning
confidence: 86%
“…Queen larvae and extracts of queen larvae were significantly less attractive than worker and drone larvae, and the royal jelly of the queen larvae even had a repellent effect (Calderone and Lin, 2001;Calderone et al, 2002;Trouiller et al, 1994). Nazzi et al (2009) confirmed these results for octanoic acid, which is present in higher quantities in royal jelly than in the food of worker or drone larvae.…”
Section: Orientation and Host Findingmentioning
confidence: 86%
“…The reproductive success of a mite is positively correlated with its host’s post-capping developmental duration. Consequently, mites prefer to parasitize drone brood over the workers and queens [ 153 , 154 ] presumably because the drones’ longer development time increases mite fitness. Drone brood suffers from higher varroa parasitism than worker brood because of active choices by the mites based on brood or food odors, or because a slower drone development and more nurse bee visits translate into more opportunities to infest drone cells [ 155 , 156 ].…”
Section: Parasites and Queen Qualitymentioning
confidence: 99%
“…Drone frames that we have investigated here were highly infested already in early summer, not least because some colonies remained untreated in the former season at our experimental apiary but also because the mite’s preference to infest drone cells is approximately eight times higher when compared to worker brood (Fuchs, 1990, Santillán-Galicia et al, 2002). In addition, the time frame which is attractive to enter cells for infestation is approximately twice as long in drone brood (Calderone et al, 2002), being one reason for this preference. Under these circumstances it was not surprising that we found many multiply infested drone cells and it became a challenge to locate cells containing only one foundress for our evaluation.…”
Section: Discussionmentioning
confidence: 99%